An introduction to accountancy, 7th edition - Maheshwari S.N., Maheshwari S.K. (Vikas publishing house. Mumbai, 2003)
Commerce
ENGLISH
Keywords: An introduction to accountancy, 7th edition; Commerce; Commerce